Childhood cancer survivorship : improving care and quality of life - Hewitt, Maria Elizabeth; Weiner, Susan Lipschitz, 1942-; Simone, Joseph V. (Online access: National Academy of Sciences National Academies Press., 2003)
Commissioned by the National Cancer Policy Board, the nine chapters in this report explore the medical, social, and economic consequences of surviving childhood cancer, identify essential elements of quality care, assess the status of applied clinical and health services research, and propose policies to improve the quality of life for childhood cancer survivors and their families. No index is provided. Annotation : 2004 Book News, Inc., Portland, OR (booknews.com).